Removal of Dissolved Organic Carbon from Oily Produced Water by Adsorption onto Date Seeds: Equilibrium, Kinetic, and Thermodynamic Studies - Al.Haddabi, M.; Vuthaluru, Hari; Znad, Hussein; Ahmed, M. (Springer International Publishing, 2015)
The feasibility of date seeds as a new low-cost natural adsorbent for the removal of dissolved organic carbon (DOC) from oily produced water was investigated. The aim of this study was to elucidate the mechanism associated with the removal of DOC and to find the best equilibrium isotherms and kinetic models for DOC removal in batch adsorption experiments. The effect of various physicochemical parameters such as initial DOC concentration (18.5–93.5 mg/L), solution pH (4–9), temperature (25–45 °C), and date seeds dosages (0.5–2.0 g) was evaluated. The equilibrium stage was attained after a contact time of 120 min. The maximum DOC removal was 82 % for 93.5 mg/L of DOC concentration. The equilibrium data were well represented by the Langmuir isotherm. The maximum monolayer adsorption capacity of date seeds was found to be 74.62 mg/g. The separation factor, R L, from the Langmuir equation and the Freundlich constant, n, indicated a favorable adsorption. The kinetic studies indicated that the adsorption process follows the pseudo-second-order kinetics. The adsorption of DOC is governed by both surface and pore diffusion. The results revealed that the DOC uptake decreases when temperature and pH increases. The adsorption process has been found exothermic in nature, and the thermodynamic parameters were determined. The Langmuir isotherm model equation was adopted to design a single-stage batch absorber for DOC adsorption onto date seeds. The study demonstrated that date seeds can be considered as a promising low-cost adsorbent for the removal of DOC from oily produced water